2015
DOI: 10.1002/maco.201508436
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin microgels as a potential corrosion inhibitor carriers for self‐healing coatings: Preparation and codeposition

Abstract: Co-deposition of a coating with capsules containing a corrosion inhibitor is one of the methods to protect the material surface against corrosion. This generation of coatings can be regenerated in response to mechanical or chemical damage. The paper presents a method for preparing gelatin microgels that can be eco-friendly corrosion inhibitor reservoir. The influence of temperature, stirring rate, an addition of surfactants (ionic and non-ionic) on microgel quality has been studied. It has been found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…After 500 cycles, Zn foil against hydrogel remains smooth and unchanged on the color and no ZHS peak was identified in XRD analysis (Figure 6E and F). Gelatin microgels have been studied as a potential corrosion inhibitor in self‐healing coatings 67 . Liu et al.…”
Section: Issues Solutions and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 500 cycles, Zn foil against hydrogel remains smooth and unchanged on the color and no ZHS peak was identified in XRD analysis (Figure 6E and F). Gelatin microgels have been studied as a potential corrosion inhibitor in self‐healing coatings 67 . Liu et al.…”
Section: Issues Solutions and Mechanismsmentioning
confidence: 99%
“…Gelatin microgels have been studied as a potential corrosion inhibitor in self-healing coatings. 67 Liu et al investigated the influence of the gelatin electrolyte additive on Zn corrosion in the mildly acidic aqueous solution. It is found that the gelatin additive with the selected concentration is capable of effectively suppressing Zn corrosion.…”
Section: Corrosion and Passivationmentioning
confidence: 99%
“…The medicinal grade stainless steel is commonly employed as biomaterial in orthopaedic implants. Surface of SS304 can be modified to achieve antimicrobial feature by applying biopolymers through dip coating, brush coating or sol-gel coating [11].…”
Section: Introductionmentioning
confidence: 99%
“…A new nickel-phosphorous self-healing coating process, which promises enhanced material properties and a low toxicity production process compared to the chromium-based equivalent is proposed [15]. The introduction of microgels comprised of nickel salts and sodium hypophosphite into Ni-P matrices results in the surface functionalisation by the introduction of self-healing properties.…”
Section: Introductionmentioning
confidence: 99%